Continuous positive airway pressure and mechanical ventilation by facemask in newborn infants. Issue 5989 (18th October 1975) - Allen, L P; Blake, A M; Durbin, G M; Ingram, D; Reynolds, E O; Wimberley, P D
Abstract : During a nine-month period 24 newborn infants were treated with continuous positive airway pressure (CPAP) or mechanical ventilation delivered through a facemask. The mask was held in place in a way that minimised trauma and distortion of the head. The median birth weight of the infants was 1096 g and their median gestational age 29 weeks.The usual reason for treatment was hyaline membrane disease or recurrent apnoea due to inadequate control of breathing. Twenty-one of the infants survived. The technique was simple to apply and complications were minimal. We suggest that it may have advantages over other methods of applying CPAP or mechanical ventilation to infants mildly affected by respiratory illnesses and that it should be useful in avoiding endotracheal intubation or reducing the length of time that infants with more serious illnesses are intubated.